2013
DOI: 10.1590/s0004-28032013000200030
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helicobacter Pylori Infection and Lifestyle Habits in the Development of Gastroduodenal Diseases in a Population From the Brazilian Amazon

Abstract: -Context -Although more than half of the world's population is colonized with Helicobacter pylori, it remains unknown why this organism is able to produce severe disease in some hosts and be innocuous in others. The clinical outcome of infection is determined by several factors, including differences in the host response to bacterial stimulation, specific virulence factors of the organism and environmental influences, or a combination of these factors. Objectives -This study compared the prevalence of H. pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…Similar results have been reported in other studies conducted in the State of Pará (31,38) and in other Brazilian states, as well as in other countries (2,11,25,40) . When only H. pylori-positive patients were compared between the four groups studied, an even stronger association was observed between infection with cagA-positive H. pylori strains and gastrointestinal diseases.…”
Section: Frequency Of Different Genotypes In Patients With Gastrointesupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results have been reported in other studies conducted in the State of Pará (31,38) and in other Brazilian states, as well as in other countries (2,11,25,40) . When only H. pylori-positive patients were compared between the four groups studied, an even stronger association was observed between infection with cagA-positive H. pylori strains and gastrointestinal diseases.…”
Section: Frequency Of Different Genotypes In Patients With Gastrointesupporting
confidence: 92%
“…Queiroz et al (24) found that, in Brazil, 95.0% and 62.3% of strains isolated from children with and without duodenal ulcers are cagA-positive, respectively. Other studies have reported a higher frequency of the cagA gene in H. pyloripositive patients with peptic ulcer and gastric cancer (17,33,38) . In the present study, 97.6% of the patients were infected with only one type of bacterial strain (monoinfection) and 2.4% were infected with more than one type of strain (mixed infection).…”
Section: Frequency Of Different Genotypes In Patients With Gastrointementioning
confidence: 85%
See 1 more Smart Citation
“…4 Inadequate dietary habits are associated with intense neutrophilia, higher degree of inflammation and with the development of gastric cancer. 20 Lastly, a recent study demonstrated a statistically significant increase in H. pylori infection among betel chewers compared to those who did not chew betel. This observation supports the hypothesis that betel chewing may affect periodontal health and thus predispose individuals to colonization with H. pylori.…”
Section: 7879mentioning
confidence: 97%
“…Besides, factors as smoking, eating habits and alcohol consumption have been associated with a higher risk of the development of peptic ulcer and gastric cancer in people infected by H. pylori. [18][19][20] The aim of this review is to provide an overview of bacterial, environmental, and host factors that influence susceptibility to severe outcomes of H. pylori infection.…”
mentioning
confidence: 99%